Government Initiative to Propose E-commerce Logistics Companies to Improve Parcel Accessibility and Scanning in Fulfillment Centers - Muhammad Younus; Achmad Nurmandi; Suswanta (Jurnal Multidisiplin West Science, 2023)
In the recent era, the rise of the Internet has brought about a significant disruption in the global economy regarding the new height of innovative businesses, which created different employment opportunities. But still, people are struggling to cope with this recent phenomenon and cannot fully utilize these solutions for their benefit. One of the most critical ways of business emerged through the Internet as E-commerce. So, people are getting so many benefits from it, but in some areas, they are still struggling to get effective results; that is why to deal with these issues and suggest a proper way forward. Therefore, this Paper's objective will be to pick and choose one of the challenges and then will provide the solutions that will fill in the gaps, and most importantly, how the government will play a vital role in the successful running and implementing of this initiative to boost the E-Commerce sector productivity.